Implementation of Blended Learning with A STEM Approach to Improve Student Scientific Literacy Skills During The Covid-19 Pandemic - Hana Lestari; Ima Rahmawati; Ridwan Siskandar; Hadi Dafenta (Postgraduate, University of Mataram, 2021)
The Covid-19 pandemic has a positive impact on the blended learning system, especially the synchronous and asynchronous aspects of online learning. This study aims to obtain information about how to apply the blended learning model with the STEM approach to students' scientific literacy skills during the COVID pandemic. The research method used was pre-experiment with one group pretest-posttest design. This research was conducted at SMAN 1 Bojong Gede, Bogor Regency in the academic year 2020/2021. The research sample used two class X which have been selected as purposive sampling. The instrument used in this study was a student science literacy test containing 20 question items. The data processing technique was carried out descriptively by calculating the mean and percentage of each item to obtain a description of the students' scientific literacy skills, then the data were analyzed inferentially with paired sample t-test using SPSS version 22 software, to see differences in scientific literacy before and after blended learning with the STEM approach. The results showed that in general, the average scientific literacy skills of students from the application of the blended learning model with the STEM approach had an average score of 85.50 in the good category. For students to have a better understanding of scientific literacy, students' understanding of science should be continuously trained through the blended learning model with the STEM approach.